The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1682/jrrd.2010.07.0138
|View full text |Cite
|
Sign up to set email alerts
|

Audiometric thresholds and prevalence of tinnitus among male veterans in the United States: Data from the National Health and Nutrition Examination Survey, 1999-2006

Abstract: Abstract-Hearing loss and tinnitus are the two most prevalent service-connected disabilities among U.S. veterans. The number of veterans receiving compensation and services from the Department of Veterans Affairs (VA) for these conditions continues to increase annually. However, the majority of veterans in the United States do not use VA medical centers or clinics for healthcare and do not receive VA compensation payments. Therefore, the prevalence of hearing loss and tinnitus among U.S. veterans is unknown. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…The most likely reason for this disparity in findings is the relatively small number of subjects in each of these studies. In order to draw definitive conclusions regarding differences in audiometric results between PD patients and age-matched control subjects, it would be necessary to collect and analyze data from much larger pools of participants (as, e.g., in [3] or [4]). However, worse thresholds for 1500 and 2000 Hz tones exhibited by PD patients in the current study reflect a pattern of hearing loss which is more likely to be noticed by patients compared to similar degrees of hearing loss at 4000 or 8000 Hz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most likely reason for this disparity in findings is the relatively small number of subjects in each of these studies. In order to draw definitive conclusions regarding differences in audiometric results between PD patients and age-matched control subjects, it would be necessary to collect and analyze data from much larger pools of participants (as, e.g., in [3] or [4]). However, worse thresholds for 1500 and 2000 Hz tones exhibited by PD patients in the current study reflect a pattern of hearing loss which is more likely to be noticed by patients compared to similar degrees of hearing loss at 4000 or 8000 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…The average age for PD onset is approximately 60 years, and the prevalence of PD increases with age [2]. Since the majority of people who are 60 years old or older have significant hearing loss (HL) and the prevalence of HL increases with age [3, 4], a majority of PD patients have significant HL that will worsen over time.…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 3-4 million U.S. military Veterans have tinnitus, of whom up to 1 million require clinical intervention [2]. It was recently reported that Veterans have twice the prevalence of tinnitus as non-Veterans [3]. The greater prevalence of tinnitus for Veterans compared with non-Veterans has also been reported by Adams et al [4].…”
Section: Introductionmentioning
confidence: 94%
“…[20] ASD development from exposure to threatening, unexpected, loud sounds in close proximity, such as explosions and weapon fire, can be expected to occur in active service, either with or without noise damage causing hearing loss. Apart from persistent TTTS symptoms, severe ASD almost always includes hyperacusis (as shown in this study), often includes tinnitus, and can lead to PTSD.…”
Section: Clinical Medico-legal and Military Implications Of Asmentioning
confidence: 99%